2021
DOI: 10.1111/jerd.12826
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of a potassium nitrate dentifrice effective in reducing tooth sensitivity related to in‐office bleaching? A randomized triple‐blind clinical trial

Abstract: Objective: The aims of this study were to evaluate whether the use of a dentifrice containing 5% potassium nitrate (KNO 3 ) prior to and during in-office dental bleaching reduces bleaching-induced tooth sensitivity and affects bleaching efficiency.Materials and methods: Thirty-eight individuals were randomly distributed into two groups (n = 19). The experimental group performed toothbrushing using a dentifrice containing 5% KNO 3 , one week before treatment and before the first and second bleaching sessions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…The ultimate test for a novel tooth whitening method would of course be to conduct a clinical study that, however, is not possible in the current status due to regulatory reasons. Teeth were not mechanically cleaned before bleaching as would be done in a clinical situation applying dentifrice (Ortega‐Moncayo et al, 2021 ) or enamel microabrasion (Bernardi et al, 2021 ). In addition, specimens were randomly allocated to the two study groups without performing any matching with respect to tooth shade and tooth type.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate test for a novel tooth whitening method would of course be to conduct a clinical study that, however, is not possible in the current status due to regulatory reasons. Teeth were not mechanically cleaned before bleaching as would be done in a clinical situation applying dentifrice (Ortega‐Moncayo et al, 2021 ) or enamel microabrasion (Bernardi et al, 2021 ). In addition, specimens were randomly allocated to the two study groups without performing any matching with respect to tooth shade and tooth type.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the efficacy of IPB [ 31 ] has been previously demonstrated by numerous research groups, post-treatment DH continues to be the most frequently reported adverse effect [ 15 , 16 , 17 ]. In fact, a previous study [ 36 ] investigating the correlation between the bleaching efficacy and risk/intensity of post-treatment DH has indicated, based on a multi-regression and logistic analysis, that the risk for the occurrence of DH was 120% more likely to precipitate from IPB than from at-home bleaching techniques [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though several reports have demonstrated the bleaching efficacy of IPB [ 4 , 5 , 6 ], other studies have indicated that the utilization of these highly caustic bleaching agents may result in the occurrence of adverse effects (short- and long-term), including irreversible changes in enamel topography [ 7 ] and chemical make-up [ 8 , 9 , 10 ], decreased surface microhardness [ 11 ], increased surface roughness [ 12 ], diminished bond strength [ 13 ], and reduced fracture resistance [ 14 ]. From the clinical standpoint, the most prevalent adverse effect reported by patients and clinicians is mild to severe dentin hypersensitivity (DH) [ 4 , 15 , 16 ]. According to previous studies, there is a strong and positive correlation between dentin hypersensitivity, HP concentration, and pulpal cytotoxicity [ 17 , 18 ], where the higher the HP concentration, the stronger the dentin hypersensitivity [ 16 ], and the effects are more durable.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that at‐home bleaching tends to offer better color stability, 15 while in‐office bleaching can produce a fast visible whitening effect following a single treatment 16 . Consequently, individuals seeking rapid outcomes or those with an aversion to customized trays may be more inclined to pursue in‐office tooth bleaching 17 . A recent meta‐analysis demonstrated that there are no significant differences in the overall effectiveness of the two types of bleaching treatment 18 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Consequently, individuals seeking rapid outcomes or those with an aversion to customized trays may be more inclined to pursue in-office tooth bleaching. 17 A recent meta-analysis demonstrated that there are no significant differences in the overall effectiveness of the two types of bleaching treatment. 18 Diverse factors, including the concentration and application time of the bleaching gel, the subject's age, the stain type, and the initial color of the tooth, contribute to individual responses to bleaching.…”
Section: Introductionmentioning
confidence: 99%